A study examining the impact of supermarket shopping online vs. In-store on family food waste (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The purpose of this research is to find out how much food waste families produce as a result of buying for groceries online vs in-store. Understanding how purchase behavior vary across various modes is vital for devising successful food-waste-reduction measures, especially with the rise of digital shopping platforms. Using data from both online and in-store shoppers, the study compares and contrasts important characteristics such shopping frequency, planning behaviors, impulsive purchasing, product visibility, and portion-size selections. The results show that online buyers are more likely to plan ahead, buy fewer impulsive items, and better manage their inventory, all of which lead to less food waste. Store marketing and visual stimulants, on the other hand, drive in-store customers to make more impulsive purchases, which means more wasted perishable goods. Targeted interventions, such as improved digital shopping tools, consumer education, and waste-reduction campaigns led by supermarkets, are needed to promote sustainable home food behaviors, according to the study.